Pollen morphological variation of Berberis L. from Pakistan and its systematic importance. Issue 9 (27th June 2019) - ur Rahman, Saeed; Khan, Shujaul Mulk; Zafar, Muhammad; Ahmad, Mushtaq; Khan, Raees; Hussain, Sajad; Khalid, Muhammad; Kayani, Sadaf‐Ilyas
Abstract: Due to overlapping and diverse morphological characters, Berberis is among the most taxonomically complex genera. Palynology is one of the taxonomic tools for delimitation and identification of complex species. In this study, pollens of 10 Berberis species were analyzed through light and scanning electron microscopy. Qualitative as well as quantitative features (pollen shape, size, presence or absence of colpi, colpi length and width, exine thickness, ornamentation, pollen class, aperture, and polar–equatorial ratio) were measured. Five species were observed to have colpate (pantocolpate) with elongated ends, radially symmetrical, isopolar, monads, and psilate‐regulate pollens. In polar view, six pollen were spheroidal, two were ovoid, one spherical, and one oblate. Similarly, variation in pollen length was prominent and the largest pollen on polar view was recorded for B. psodoumbellata 60–65 μm (62.4 ± 0.9), while the smallest one was observed for B. lycium 29–35 μm (32.2 ± 1). The observed variation in both quantitative and qualitative features were important in taxonomic identification. This shows that palynological characters are helpful in identification of Berberis genus at the species level. Abstract : Light and scanning electron microscopic investigation of the pollens of 10 Pakistani Berberis L. species for the first time. The investigated characters were found useful to resolve the taxonomic complexity of the genus.